The complete mitochondrial genome of the Indian dammer bee, Tetragonula iridipennis, and the phylogenomics of Meliponini - Karuppaiah, Vadivelu; Gadge, Ankush S.; Shirsat, Dhananjay V.; Soumia, Parakkattu S.; Mainkar, Pawan; Kumar, Satish; Jaiswal, Durgesh K.; Mahajan, Vijay (Frontiers in Ecology and Evolution, 2023)
The Indian stingless bee Tetragonula iridipennis (Hymenoptera: Apidae), popularly recognized as the Indian dammer bee, is an economically important and widely distributed non-Apis bee species in India. The taxonomic gaps, systematics, evolutionary puzzles, and structural motifs within the mitogenomes of this species have rarely been examined and are not fully understood. Next-generation sequencing was employed to decipher the complete mitochondrial genome of T. iridipennis (15,045 bp). De novo genome assembly revealed that it encompasses 34 genes: protein-coding genes (13), transfer RNA (tRNAs) genes (19), and ribosomal RNA (rRNA) genes (2). Additionally, genome organization, including gene content, nucleotide composition, codon usage, and gene rearrangement, was investigated to better comprehend, utilize, and conserve this germplasm resource. The average gene length was 400 bp; maximum and minimum lengths were 1,530 bp (cox1) and 57 bp (tRNA-S1), respectively. Phylogenetic analysis has suggested that T. iridipennis is mostly closely related to T. pagdeni and Lepidotrigona species. All the stingless bee species (Meliponini) formed a distinct clade that shared a closer relationship with bumble bees (Bombini) than honey bees (Apini). The nucleotide composition of T. iridipennis was biased toward A+T, which accounted for 75.95% of the whole mitogenome. Length and compositional differences between T. iridipennis and other bees were detected, and gene order was compared. The mitogenome of T. iridipennis showed the highest gene rearrangement score (78), suggesting this species has a hyperactive evolutionary history. The variations of gene positions and gene rearrangement in the mitogenome could also aid in resolving the phylogenetic relationships and evolutionary history in Meliponini. Additionally, this is the first report of a complete mitochondrial genome sequence of T. iridipennis.